2015
DOI: 10.1016/j.jams.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Could Acupuncture Be Useful in the Treatment of Temporomandibular Dysfunction?

Abstract: In this study, the effects of acupuncture in comparison with flat occlusal plane appliance were evaluated in patient with myogenic temporomandibular dysfunction (TMD). The sample consisted of 40 women with TMD and unbalanced energy predominance of Yang Liver Ascension, selected using the Renying and Cunkou pulses, randomly divided into two groups: acupuncture and splint. The effect of treatments on the masseter and anterior temporal muscles was evaluated after 4 weeks of treatment, by means of electromyographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 20 publications
0
47
1
6
Order By: Relevance
“…All studies evaluated the outcomes at baseline and after the treatment protocol 61 , with number of sessions varying from 1 week to 1 year. Pain levels were assessed as the primary outcome in all studies using Visual Analogic Scale (VAS) in 29 (83%) studies 1,2,10,15,16,22,24,25,31,33,36,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][61][62][63][64] or an algometer to evaluate the pressure pain threshold in 5 (14%) studies 2,36,46,58,62 ; one study (3%) used the Verbal Pain Scale 59 . The results of an intragroup analysis demonstrated that 27 (77%) 5,10,20,22,24,25,27,31,33,36,44...…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies evaluated the outcomes at baseline and after the treatment protocol 61 , with number of sessions varying from 1 week to 1 year. Pain levels were assessed as the primary outcome in all studies using Visual Analogic Scale (VAS) in 29 (83%) studies 1,2,10,15,16,22,24,25,31,33,36,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][61][62][63][64] or an algometer to evaluate the pressure pain threshold in 5 (14%) studies 2,36,46,58,62 ; one study (3%) used the Verbal Pain Scale 59 . The results of an intragroup analysis demonstrated that 27 (77%) 5,10,20,22,24,25,27,31,33,36,44...…”
Section: Discussionmentioning
confidence: 99%
“…The results of an intragroup analysis demonstrated that 27 (77%) 5,10,20,22,24,25,27,31,33,36,44,45,46,47,50,[52][53][54][55][56][57][58][59][60][61][62][63] of the studies presented reduction in pain and 22 (62%) 2,5,10,15,20,24,25,31,36,[44][45][46][47][52][53][54]56,57,59,60,62,64 , improvement in function. Among them, LLLT (34%) 2,515,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acupuncture, Botox injections, Chiropractic/Osteopath jaw manipulations and other treatments have been tried in TMD management but have yet to be accepted into mainstream practice due to lack of evidence in the effectiveness of these modalities …”
Section: Treatment Of Temporomandibular Disorders (Table )mentioning
confidence: 99%